Chemical potential of gaseous medium for corundum single crystals growth - Kryvonosov, Ie.; Lytvynov, L. (Functional Materials, 2018)
A method has been proposed for evaluation of the chemical potential (ε) of the medium for corundum growth and annealing. It is based on the difference between aluminum and oxygen chemical potentials in corundum thermal dissociation products and technological medium. Disturbance of the anionic desstoichiometry of the crystal in the high-temperature carbon-containing medium is defined by lowered oxygen partial pressure over the crystal surface due to the interaction of corundum thermal dissociation products with carbon monoxide contained in the growth medium. The function [VO] = f(ε) has been determined, which makes it possible to calculate the chemical potential of the gas medium of the process equipment on the basis of data on the violation of stoichiometry of the grown (annealed) sapphire. Evaluated is the chemical potential of the gaseous medium for the grown and annealing of corundum single crystals for various technological systems.